Optical and electronic properties of (InxGa1−x)2O3 alloys - Shrestha, Bishal; Mainali, Madan K.; Dulal, Prabin; Jamarkattel, Manoj K.; Quader, Abdul; Bastola, Ebin; Phillips, Adam B.; Heben, Michael J.; Podraza, Nikolas J. (Journal of applied physics, 2025)
Indium gallium oxide [(InxGa1−x)2O3] alloys are of interest for a variety opto-electronic applications including photovoltaic devices owing to the ability to control properties through alloy composition. A thorough evaluation of the opto-electronic properties of (InxGa1−x)2O3 (x = 0.71, 0.55, 0.45, 0.36, and 0.28) thin films is obtained by using terahertz to ultraviolet range spectroscopic ellipsometry to measure the complex dielectric function (ɛ = ɛ1 + iɛ2) spectra from 0.400 meV to 5.877 eV and the derived vibrational modes from chemical bonding, inter-band transition energies, and carrier transport properties. Optical band edges of direct and non-direct transitions increase from 3.82 to 4.14 eV and 2.96 to 3.36 eV, respectively, with decreasing In-content, whereas the carrier concentration determined from the direct electrical Hall effect and spectroscopic ellipsometry measurements decreases from ∼1020 to 1018 cm−3. Mobilities (μSE), resistivities (ρSE), and carrier effective masses (m*SE) from the spectroscopic ellipsometry range from ∼10.6 to ∼66.8 cm2 V−1 s−1, 2.3 × 10−3, to 47.1 × 10−3 Ω cm, and 0.308 to 0.397 me, respectively. μSE and ρSE are compared to those obtained from the direct electrical Hall effect and four-point probe measurements with discrepancies attributed to principles of measurement techniques. Spectroscopic ellipsometry determined parameters are representative of properties within localized regions, whereas direct electrical measurements are influenced by a greater degree of charge carrier scattering due to longer path lengths of travel.